2001
DOI: 10.1093/jn/131.8.2082
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Juice Supplementation to Atherosclerotic Mice Reduces Macrophage Lipid Peroxidation, Cellular Cholesterol Accumulation and Development of Atherosclerosis

Abstract: Inhibition of lipid peroxidation contributes to the attenuation of macrophage cholesterol accumulation, foam-cell formation and atherosclerosis. Evidence suggests that nutritional antioxidants such as pomegranate juice (PJ) can contribute to the reduction of oxidative stress and atherogenesis. The goals of the present study were to determine whether such beneficial effects of PJ exist when supplemented to apolipoprotein E-deficient (E(0)) mice with advanced atherosclerosis and to analyze the antiatheroscleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
208
3
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(226 citation statements)
references
References 45 publications
13
208
3
2
Order By: Relevance
“…However, Nunez-Selles (2005) reported that phenolic compounds were found in significant concentration in mango seed kernel and barks to be responsible for antioxidant activity. For phenolic constituents in kernel pomegranate fruits are diver than that reported by several researchers, that the major phenolic compounds were punicalagin, ellagic acid, gallo-tannins and anthocyanins (Kaplan et al, 2001;Noda et al, 2002;Cerda et al, 2003). However, the results agree with that the main phenolics in pomegranate were gallic and ellagic acids (Huang et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
“…However, Nunez-Selles (2005) reported that phenolic compounds were found in significant concentration in mango seed kernel and barks to be responsible for antioxidant activity. For phenolic constituents in kernel pomegranate fruits are diver than that reported by several researchers, that the major phenolic compounds were punicalagin, ellagic acid, gallo-tannins and anthocyanins (Kaplan et al, 2001;Noda et al, 2002;Cerda et al, 2003). However, the results agree with that the main phenolics in pomegranate were gallic and ellagic acids (Huang et al, 2005).…”
Section: Discussionsupporting
confidence: 54%
“…The biological properties associated with pomegranate fruits [7][8][9][10] prompted us to evaluate their major phytochemical ingredients as single purified compounds, punicalagin and EA (Fig. 1), and as combinations, TPT and PJ.…”
Section: Resultsmentioning
confidence: 99%
“…Pomegranate juice and extracts have been shown to have potent in vitro antioxidant [7,24] and in vivo anti-atherosclerotic properties [8,9,15], attributed to its high content of polyphenols including ETs and EA. Recently, there have also been numerous reports on the in vitro and in vivo anticancer properties of pomegranates [10,[25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Dietary supplementation of polyphenol-rich pomegranate juice to atherosclerotic mice significantly inhibited the development of atheroclerotic lesions and this may be attributed to the protection of low-density lipoprotein against oxidation. 13,14 Fermented pomegranate juice and coldpressed PFE can reduce prostaglandin and leukotriene formation by inhibition of cyclooxygenase and lipoxygenase activities. 15 Recent studies have shown that pomegranate wine may serve as a potent inhibitor of nuclear factor kappa B (NF-B) in vascular endothelial cells.…”
mentioning
confidence: 99%